CuO Nanoparticles : Biosynthesis, Characterization and In Vitro Study - Ahmad Fatoni; Reza Agung Sriwijaya; Umy Habiba; Nurlisa Hidayati (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
The biosynthesis of CuO nanoparticles was studied. The aims of this research were biosynthesis CuO nanoparticles from Cu2+ion solution and leaves aquoeus extract of sweet star fruit and its in vitro study as antibacterial agent of Escherichia coli. CuO nanoparticles was characterized using FTIR spectroscopy and X-Ray diffractometer. CuO nanoparticles was synthesized by reaction between Cu2+ion solution and leaves aquoeus extract of sweet star fruit. Paper disk method was used as the application of the suspension of CuO nanoparticles. The result showed that Cu-O groups detected at wave number of 503, 619, 767 and 821 cm-1. Diffractogram of CuO nanoparticles had sharp and narrow diffraction peaks. The crystallite size of CuO nanoparticles was 4.25 nm. The average inhibition zone of CuO nanoparticles at concentration 10.000, 7.500, 5.000 and 2.500 ppm was 17.43 ± 1.81 ; 15.73 ± 0.40 ; 14.50 ± 2.96 and 9.67 ± 0.28 mm respectively.